2018
DOI: 10.3390/mi9030116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3D-Printed Moulds for Soft Lithography of Millifluidic Devices

Abstract: Increased demand for inexpensive and rapid prototyping methods for micro- and millifluidic lab-on-a-chip (LOC) devices has stimulated considerable interest in alternative cost-effective fabrication techniques. Additive manufacturing (AM)—also called three-dimensional (3D) printing—provides an attractive alternative to conventional fabrication techniques. AM has been used to produce LOC master moulds from which positive replicas are made using soft-lithography and a biocompatible elastomer, poly(dimethylsiloxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Briefly, a mixture of elastomer base and curing agent (10:1 ratio w/w) was degassed to remove any residual air bubbles and poured on an SU‐8 relief pattern to achieve a device thickness of 3–5 mm. PDMS was thermally cured at 70°C for 2 h . Cured PDMS devices were bonded to a standard borosilicate glass microscope slide via oxygen plasma surface activation and interfaced with peristaltic pumps using standard microfluidic interconnects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, a mixture of elastomer base and curing agent (10:1 ratio w/w) was degassed to remove any residual air bubbles and poured on an SU‐8 relief pattern to achieve a device thickness of 3–5 mm. PDMS was thermally cured at 70°C for 2 h . Cured PDMS devices were bonded to a standard borosilicate glass microscope slide via oxygen plasma surface activation and interfaced with peristaltic pumps using standard microfluidic interconnects.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, laser ablation and machining of polymers such as PMMA is prone to cracking and chipping during milling resulting in prototypes with much higher surface roughness than other approaches. More recently additive manufacturing (AM) and in particular stereolithography (SLA) technology has been proposed as an innovative technique to advance prototyping of chip‐based devices with high aspect ratios . However, several most recent studies have identified that significant amounts of toxic photoinitiator residues may leach from proprietary AM materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free radicals migrate from one monomer to another in the course of chain growth. Radical polymerization stops, when two radicals, or creating polymer chains, or fragments of initiators combine [3]. PC can contain several photoinitiators, which enables to simultaneously enhance the efficiency of polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Among AM technologies, stereolithography (SL) and micro-stereolithography (MSL) [1,2,3] (i.e., SL in micro-scale) are widely utilized in many domains, owing to the high resolution, precision, and adaptability of the increasing number of materials. Specifically, these developments enable the precise fabrication of biomaterial scaffold [4], bioprinting [5], and microfluidic devices [6]. With the advance of MSL, more stringent fabrication demands are posed.…”
Section: Introductionmentioning
confidence: 99%